Porous carbon material and preparation method thereof, electrode and preparation method thereof, and supercapacitor

By using 2,9-dimethylquinacridone and KCl/K2CO3 pyrolysis to prepare porous carbon materials, the problems of complex preparation, high cost and environmental pollution in the existing technology of porous carbon materials are solved. High yield, low ash content and stable structure of porous carbon materials are achieved, which improves the electrochemical performance of supercapacitors.

CN119284900APending Publication Date: 2025-01-10SOUTH CHINA UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411250439.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing methods for preparing porous carbon materials are complex, costly, cause serious environmental pollution, have low yields, and have underdeveloped pore structures, making it difficult to meet the practical application requirements of supercapacitors.

Method used

Porous carbon materials were prepared by pyrolysis using 2,9-dimethylquinacridone as a carbon precursor and KCl and K2CO3 as activators. The structure and porosity of the materials were optimized, and conductive components and binders were added to form electrodes.

Benefits of technology

The prepared porous carbon material has low ash content, large specific surface area, and stable structure. As an electrode material, it exhibits high specific capacitance and excellent cycle stability in supercapacitors, making it suitable for large-scale industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119284900A_ABST
    Figure CN119284900A_ABST
Patent Text Reader

Abstract

The invention discloses a porous carbon material and a preparation method thereof, an electrode and a preparation method thereof, and a supercapacitor. The preparation method of the porous carbon material provided by the invention comprises the following steps: mixing 2, 9-dimethyl quinacridone, KCl and K2CO3, and performing pyrolysis in a protective atmosphere to obtain the porous carbon material. The porous carbon material is prepared by taking 2, 9-dimethyl quinacridone as a carbon precursor and compounding KCl and K2CO3 as an activating agent, the preparation method has the advantages of simplicity in operation, greenness, environmental protection, high yield of the porous carbon material and the like, and the prepared porous carbon material is low in ash content, large in specific surface area, rich in pore structure, stable in structure, low in cost and suitable for industrial production. The supercapacitor made of the porous carbon material as an electrode material is high in specific capacity value and capacity retention rate and excellent in cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of energy storage technology, and in particular to a porous carbon material and a preparation method thereof, an electrode and a preparation method thereof, and a supercapacitor. Background Art

[0002] Supercapacitors are a new type of energy storage device that combines the high specific energy of batteries with the high specific power of traditional capacitors. They have very broad application prospects in the field of energy storage. Supercapacitors achieve high capacitance by accumulating charges on the surface of electrodes, so electrode materials are one of the most important components of supercapacitors. The electrode material determines the capacitance of supercapacitors. The development of suitable electrode materials is expected to overcome the defect that supercapacitors have lower energy density than batteries. Porous carbon has the advantages of rich pore structure, large specific surface area, good conductivity, stable physical and chemical properties, and low production cost. It is considered to be one of the most promising electrode materials for supercapacitors.

[0003] At present, the precursors used to prepare porous carbon materials mainly include fossil energy, biomass, organic polymers, etc. The regeneration rate of fossil energy is slow, and it is gradually in short supply, and the environmental pressure caused by it is increasing year by year. The solubility of biomass is poor, the pore structure is unstable, and the pore collapse is prone to occur, resulting in a decrease in the specific surface area of ​​the porous carbon material. In addition, the composition of biomass is complex, the pretreatment process is cumbersome, the molecular structure is uncertain, and the heteroatom content and types are limited. The solubility of organic polymers is poor, and the polymerization process is complex and slow, which seriously limits their large-scale application. In contrast, organic dyes, as small organic molecules, have the advantages of small molecular weight, high reactivity, determined chemical composition and molecular structure, and have strong plasticity, wide accessibility and long-term sustainability. There are many types, which can provide rich precursor selection and more flexible preparation methods. In addition, different organic dyes have unique structures and functional groups, which can micro-regulate the structure of porous carbon materials and are more suitable as precursors of porous carbon materials. However, organic dyes have poor structural stability and are prone to thermal decomposition when directly carbonized under high temperature conditions, resulting in low yield and specific surface area of ​​porous carbon materials. The pore structure of the obtained porous carbon materials is not well developed, making it difficult to fully meet the requirements of practical applications. In addition, existing porous carbon material preparation methods generally have problems such as relatively complex operation procedures, high costs, easily corroded equipment, environmental toxicity, and low yield of porous carbon materials, which seriously limit the practical application of porous carbon materials.

[0004] Therefore, it is of great significance to develop a method for preparing porous carbon materials with simple operation, green environmental protection, high porous carbon material yield, and to prepare porous carbon materials with high purity, low ash content, excellent electrode performance and low cost. Summary of the invention

[0005] The object of the present invention is to provide a porous carbon material and a preparation method thereof, an electrode and a preparation method thereof, and a supercapacitor.

[0006] The technical solution adopted by the present invention is:

[0007] A method for preparing a porous carbon material comprises the following steps: mixing 2,9-dimethylquinacridone, KCl and K2CO3 and placing the mixture in a protective atmosphere for pyrolysis to obtain a porous carbon material.

[0008] Preferably, the ratio of the mass of the 2,9-dimethylquinacridone to the total mass of KCl and K2CO3 is 1:1-20.

[0009] Further preferably, the ratio of the mass of the 2,9-dimethylquinacridone to the total mass of KCl and K2CO3 is 1:3-7.

[0010] Preferably, the mass ratio of KCl to K2CO3 is 1:0.1-10.

[0011] Further preferably, the mass ratio of KCl to K2CO3 is 1:0.2-5.

[0012] Preferably, the mixing method is grinding, and the grinding time is 5 minutes to 60 minutes.

[0013] Preferably, the protective atmosphere is an argon atmosphere or a nitrogen atmosphere, and the flow rate of the protective atmosphere is 100 mL / min to 300 mL / min.

[0014] Preferably, the pyrolysis is carried out at a temperature of 500° C. to 1000° C., and the pyrolysis time is 1 h to 3 h.

[0015] Preferably, the product obtained by pyrolysis is further acid-washed, water-washed and dried.

[0016] Preferably, the washing liquid used for the pickling is at least one of hydrochloric acid, sulfuric acid and nitric acid.

[0017] A porous carbon material is made by the above preparation method.

[0018] An electrode comprises the porous carbon material.

[0019] Preferably, the composition of the electrode further includes a conductive component and a binder.

[0020] Preferably, the conductive component is at least one of conductive carbon black, acetylene black, porous carbon and graphene.

[0021] Preferably, the binder is polytetrafluoroethylene (PTFE).

[0022] Preferably, the mass ratio of the porous carbon material to the conductive component is 5 to 9:1.

[0023] A method for preparing the electrode as described above comprises the following steps:

[0024] 1) mixing the porous carbon material, the conductive component and the binder solution, and then adding a demulsifier to demulsify to obtain a coating material;

[0025] 2) Apply the coating material on the carrier, dry it, and press it into sheets to obtain the electrode.

[0026] Preferably, the demulsifier used in the demulsification in step 1) is at least one of ethanol, acetone and ether.

[0027] Preferably, the amount of the demulsifier used is 10 to 20 times the mass of the binder.

[0028] Preferably, the carrier in step 2) is one of nickel mesh, titanium mesh, stainless steel mesh, titanium foil and copper foil.

[0029] Preferably, the drying in step 2) is carried out at a temperature of 60° C. to 150° C., and the drying time is 2 h to 12 h.

[0030] Preferably, the tableting in step 2) is carried out at a pressure of 5 MPa to 30 MPa.

[0031] A supercapacitor comprises the electrode.

[0032] The beneficial effects of the present invention are as follows: the present invention uses 2,9-dimethylquinacridone as a carbon precursor and a composite of KCl and K2CO3 as an activator to prepare a porous carbon material. The preparation method has the advantages of simple operation, green environmental protection, high yield of porous carbon materials, etc., and the prepared porous carbon material has low ash content, large specific surface area, rich pore structure, stable structure, and low cost. The supercapacitor made of the porous carbon material as an electrode material has high specific capacity value and capacity retention rate and excellent cycle stability.

[0033] Specifically:

[0034] 1) The present invention uses 2,9-dimethylquinacridone as a carbon precursor to prepare a porous carbon material, which has high reactivity and a unique chemical composition and molecular structure, and can micro-regulate the structure of the porous carbon material;

[0035] 2) The present invention uses KCl and K2CO3 as a composite activator to prepare a porous carbon material. The activator is green, safe and inexpensive. A porous carbon material with low ash content, large specific surface area, rich pore structure and stable structure can be prepared in a high yield by one-step pyrolysis;

[0036] 3) The supercapacitor made of the porous carbon material of the present invention as an electrode material has high specific capacity value and capacity retention rate, excellent cycle stability, and is suitable for large-scale industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is the TG curve of the porous carbon material in Example 1.

[0038] Figure 2 The cyclic voltammetry curves of the electrodes in Examples 1 to 5 and Comparative Examples 1 to 3 are shown.

[0039] Figure 3 The constant current charge and discharge curves of the electrodes in Examples 1 to 5 and Comparative Examples 1 to 3 are shown.

[0040] Figure 4 The specific capacity-current density relationship curves of the electrodes in Examples 1 to 5 and Comparative Examples 1 to 3 are shown.

[0041] Figure 5 The electrochemical impedance spectroscopy curves of the electrodes in Examples 1 to 5 and Comparative Examples 1 to 3 are shown.

[0042] Figure 6 1 is the cyclic voltammetry curve of the electrode in Example 1 at different scan rates.

[0043] Figure 7 The constant current charge and discharge curves of the electrode in Example 1 at different current densities.

[0044] Figure 8 The cyclic voltammetry curves of the electrodes in Examples 5 to 9 and Comparative Examples 1 to 3 are shown.

[0045] Fig. 9 The constant current charge and discharge curves of the electrodes in Examples 5 to 9 and Comparative Examples 1 to 3 are shown.

[0046] Fig.10 The specific capacity-current density relationship curves of the electrodes in Examples 5 to 9 and Comparative Examples 1 to 3 are shown.

[0047] Fig.11 The electrochemical impedance spectroscopy curves of the electrodes in Examples 5 to 9 and Comparative Examples 1 to 3 are shown.

[0048] Fig.12 1 is the cyclic voltammetry curve of the electrode in Example 9 at different scan rates.

[0049] Fig.13 The constant current charge and discharge curves of the electrode in Example 9 at different current densities.

[0050] Fig.14The cyclic voltammetry curves of the electrodes in Example 1, Example 9 and Comparative Examples 4 to 6 are shown.

[0051] Fig.15 The constant current charge and discharge curves of the electrodes in Example 1, Example 9 and Comparative Examples 4 to 6.

[0052] Fig.16 Specific capacity-current density relationship curves of the electrodes in Example 1, Example 9 and Comparative Examples 4-6.

[0053] Fig.17 The electrochemical impedance spectroscopy curves of the electrodes in Example 1, Example 9 and Comparative Examples 4-6 are shown. DETAILED DESCRIPTION

[0054] The present invention will be further explained and illustrated below in conjunction with specific embodiments.

[0055] Embodiment 1:

[0056] A porous carbon material, the preparation method of which is as follows:

[0057] 2,9-dimethylquinacridone, KCl and K2CO3 were mixed and ground for 35 minutes, the ratio of the mass of 2,9-dimethylquinacridone to the total mass of KCl and K2CO3 was 1:5, and the mass ratio of KCl to K2CO3 was 1:5. Then they were loaded into a corundum crucible and placed in a tubular furnace, and nitrogen was introduced at a flow rate of 200 mL / min. The mixture was kept at room temperature for 1 hour (the air in the tubular furnace was exhausted to ensure that the subsequent heating process was always in an oxygen-free environment to avoid uncontrollable volatilization of the carbon precursor and the decrease in the yield of the porous carbon material). The heating rate was then controlled to be 5°C / min from room temperature to 700°C, and the mixture was kept warm for 2 hours. The product was washed with 1 mol / L hydrochloric acid, and then washed with deionized water until the washing liquid was neutral, and then placed in a constant temperature drying oven and baked at 80°C for 10 hours to obtain a porous carbon material.

[0058] Performance Test:

[0059] The porous carbon material in this embodiment is placed in an air atmosphere for combustion and thermogravimetric analysis and heat loss test. The obtained thermogravimetric (TG) curve is as follows: Figure 1 shown.

[0060] Depend on Figure 1 It can be seen that the residues of the porous carbon material after combustion in an air atmosphere are only 0.93% (700℃), 0.76% (800℃) and 0.61% (900℃). The heat loss process is relatively simple, which is more significant at 400℃~700℃. There is only one obvious weight loss peak. After 700℃, the mass of the residue gradually tends to be stable, indicating that the ash content of the porous carbon material is low and the purity is high.

[0061] An electrode, the preparation method of which is as follows:

[0062] 1) The porous carbon material and the conductive carbon black are mixed and ground evenly as an active material, the mass ratio of the porous carbon material to the conductive carbon black is 8:1, and the active material is stirred and dispersed in a polytetrafluoroethylene aqueous solution with a mass fraction of 10%, the mass ratio of the polytetrafluoroethylene solution to the active material is 1:9, and then anhydrous ethanol is added for demulsification (to make the small droplets of the emulsion condense into agglomerates), the amount of anhydrous ethanol used is 20 times the mass of the polytetrafluoroethylene, to obtain a coating material;

[0063] 2) The coating material is applied on a nickel mesh (coating area is 1 cm×1 cm), and then placed in a constant temperature drying oven at 80°C for 4 hours, and then pressed at a pressure of 20 MPa for 5 minutes to obtain an electrode.

[0064] Embodiment 2:

[0065] A porous carbon material is identical to Example 1 except that the mass ratio of KCl to K2CO3 is adjusted from "1:5" to "1:4" during preparation.

[0066] An electrode is identical to the electrode in Example 1 except that the porous carbon material in this example is used in its preparation.

[0067] Embodiment 3:

[0068] A porous carbon material is identical to Example 1 except that the mass ratio of KCl to K2CO3 is adjusted from "1:5" to "1:3" during preparation.

[0069] An electrode is identical to the electrode in Example 1 except that the porous carbon material in this example is used in its preparation.

[0070] Embodiment 4:

[0071] A porous carbon material is identical to Example 1 except that the mass ratio of KCl to K2CO3 is adjusted from "1:5" to "1:2" during preparation.

[0072] An electrode is identical to the electrode in Example 1 except that the porous carbon material in this example is used in its preparation.

[0073] Embodiment 5:

[0074] A porous carbon material is identical to Example 1 except that the mass ratio of KCl to K2CO3 is adjusted from "1:5" to "1:1" during preparation.

[0075] An electrode is identical to the electrode in Example 1 except that the porous carbon material in this example is used in its preparation.

[0076] Embodiment 6:

[0077] A porous carbon material is identical to Example 1 except that the mass ratio of KCl to K2CO3 is adjusted from "1:5" to "2:1" during preparation.

[0078] An electrode is identical to the electrode in Example 1 except that the porous carbon material in this example is used in its preparation.

[0079] Embodiment 7:

[0080] A porous carbon material is exactly the same as Example 1 except that the mass ratio of KCl to K2CO3 is adjusted from "1:5" to "3:1" during preparation.

[0081] An electrode is identical to the electrode in Example 1 except that the porous carbon material in this example is used in its preparation.

[0082] Embodiment 8:

[0083] A porous carbon material is identical to Example 1 except that the mass ratio of KCl to K2CO3 is adjusted from "1:5" to "4:1" during preparation.

[0084] An electrode is identical to the electrode in Example 1 except that the porous carbon material in this example is used in its preparation.

[0085] Embodiment 9:

[0086] A porous carbon material is identical to Example 1 except that the mass ratio of KCl to K2CO3 is adjusted from "1:5" to "5:1" during preparation.

[0087] An electrode is identical to the electrode in Example 1 except that the porous carbon material in this example is used in its preparation.

[0088] Comparative Example 1: (No activator was used, and pyrolysis was carried out directly)

[0089] A porous carbon material, the preparation method of which is as follows:

[0090] 2,9-Dimethylquinacridone was loaded into a corundum crucible and placed in a tubular furnace. Nitrogen was introduced at a flow rate of 200 mL / min and maintained at room temperature for 1 hour. The temperature was then raised from room temperature to 700°C at a heating rate of 5°C / min and maintained for 2 hours. The product was then washed with 1 mol / L hydrochloric acid and then washed with deionized water until the washing liquid was neutral. The product was then placed in a constant temperature drying oven and dried at 80°C for 10 hours to obtain a porous carbon material.

[0091] An electrode is identical to the electrode in Example 1 except that the porous carbon material in this comparative example is used in its preparation.

[0092] Comparative Example 2: (activator is KCl)

[0093] A porous carbon material, the preparation method of which is as follows:

[0094] 2,9-dimethylquinacridone and KCl were mixed and ground for 35 minutes. The mass ratio of 2,9-dimethylquinacridone to KCl was 1:5. The mixture was then loaded into a corundum crucible and placed in a tube furnace. Nitrogen was introduced at a flow rate of 200 mL / min and kept at room temperature for 1 hour. The temperature was then raised from room temperature to 700°C at a heating rate of 5°C / min and kept at that temperature for 2 hours. The product was then washed with 1 mol / L hydrochloric acid and then washed with deionized water until the washing liquid was neutral. The product was then placed in a constant temperature drying oven and dried at 80°C for 10 hours to obtain a porous carbon material.

[0095] An electrode is identical to the electrode in Example 1 except that the porous carbon material in this comparative example is used in its preparation.

[0096] Comparative Example 3: (activator is K2CO3)

[0097] A porous carbon material, the preparation method of which is as follows:

[0098] 2,9-dimethylquinacridone and K2CO3 were mixed and ground for 35 minutes. The mass ratio of 2,9-dimethylquinacridone to K2CO3 was 1:5. The mixture was then loaded into a corundum crucible and placed in a tube furnace. Nitrogen was introduced at a flow rate of 200 mL / min and kept at room temperature for 1 hour. The temperature was then raised from room temperature to 700°C at a heating rate of 5°C / min and kept at that temperature for 2 hours. The product was then washed with 1 mol / L hydrochloric acid and then washed with deionized water until the washing liquid was neutral. The product was then placed in a constant temperature drying oven and dried at 80°C for 10 hours to obtain a porous carbon material.

[0099] An electrode is identical to the electrode in Example 1 except that the porous carbon material in this comparative example is used in its preparation.

[0100] Comparative Example 4: (activator is KOH)

[0101] A porous carbon material, the preparation method of which is as follows:

[0102] 1) 2,9-dimethylquinacridone was placed in a corundum crucible and placed in a tube furnace, and nitrogen was introduced at a flow rate of 200 mL / min, and kept at room temperature for 1 hour, and then the temperature was raised from room temperature to 400°C at a heating rate of 5°C / min, and kept at that temperature for 2 hours, and then cooled to room temperature and ground for 20 minutes to obtain a pre-carbonized product;

[0103] 2) The pre-carbonized product and KOH were mixed and ground for 35 minutes, the mass ratio of the pre-carbonized product to KOH was 1:5, and then loaded into a corundum crucible and placed in a tubular furnace, and nitrogen was introduced at a flow rate of 200 mL / min, kept at room temperature for 1 hour, and then the heating rate was controlled to be 5°C / min from room temperature to 700°C, and kept warm for 2 hours, and then the product was washed with 1 mol / L hydrochloric acid, and then the product was washed with deionized water until the washing liquid was neutral, and then placed in a constant temperature drying oven at 80°C for 10 hours to obtain a porous carbon material.

[0104] An electrode is identical to the electrode in Example 1 except that the porous carbon material in this comparative example is used in its preparation.

[0105] Comparative Example 5: (Activator is ZnCl2)

[0106] A porous carbon material, the preparation method of which is as follows:

[0107] 1) 2,9-dimethylquinacridone and ZnCl2 are loaded into a corundum crucible, the mass ratio of 2,9-dimethylquinacridone to ZnCl2 is 1:5, and then anhydrous ethanol is added and stirred thoroughly, the mass ratio of 2,9-dimethylquinacridone to anhydrous ethanol is 1:3, and a slurry mixture is obtained;

[0108] 2) The slurry mixture is loaded into a corundum crucible and placed in a tubular furnace, and nitrogen is introduced at a flow rate of 200 mL / min, and maintained at room temperature for 1 hour. The temperature is then raised from room temperature to 300°C at a heating rate of 1°C / min (to completely volatilize the anhydrous ethanol), and then the temperature is further raised to 700°C at a heating rate of 5°C / min, and maintained for 2 hours. The product is then washed with 1 mol / L hydrochloric acid, and then washed with deionized water until the washing liquid is neutral, and then placed in a constant temperature drying oven and baked at 80°C for 10 hours to obtain a porous carbon material.

[0109] An electrode is identical to the electrode in Example 1 except that the porous carbon material in this comparative example is used in its preparation.

[0110] Comparative Example 6: (activator is H3PO4)

[0111] A porous carbon material, the preparation method of which is as follows:

[0112] 1) 2,9-dimethylquinacridone and H3PO4 are charged into a corundum crucible, the mass ratio of 2,9-dimethylquinacridone to H3PO4 is 1:5, and then anhydrous ethanol is added and stirred thoroughly, the mass ratio of 2,9-dimethylquinacridone to anhydrous ethanol is 1:3, to obtain a slurry mixture;

[0113] 2) The slurry mixture is loaded into a corundum crucible and placed in a tubular furnace, and nitrogen is introduced at a flow rate of 200 mL / min, and maintained at room temperature for 1 hour. The temperature is then raised from room temperature to 300°C at a heating rate of 1°C / min, and then the temperature is further raised to 700°C at a heating rate of 5°C / min, and maintained for 2 hours. The product is then washed with 1 mol / L hydrochloric acid, and then washed with deionized water until the washing liquid is neutral, and then placed in a constant temperature drying oven and baked at 80°C for 10 hours to obtain a porous carbon material.

[0114] An electrode is identical to the electrode in Example 1 except that the porous carbon material in this comparative example is used in its preparation.

[0115] Performance Test:

[0116] 1) Cyclic voltammetry test: The electrodes in Examples 1 to 5 and Comparative Examples 1 to 3 were subjected to cyclic voltammetry tests using an electrochemical workstation model chi660e, with a scanning potential range of -1 V to 0 V and a scanning speed of 10 mV / s. The obtained cyclic voltammetry curves are shown in FIG. Figure 2 shown.

[0117] Depend on Figure 2 It can be seen that:

[0118] a) The area enclosed by the cyclic voltammetry curves of the electrodes in Examples 1 to 5 is significantly larger than that of the electrodes in Comparative Examples 1 to 3, indicating that the electrodes in Examples 1 to 5 have higher specific capacity values;

[0119] b) As the proportion of K2CO3 in the activator increases, the specific capacity of the electrode also increases. The cyclic voltammetry curve of the electrode in Example 1 (KCl:K2CO3=1:5) has the largest enclosed area and the highest specific capacitance;

[0120] c) The symmetry of the cyclic voltammetry curves of the electrodes in Examples 1 to 5 is significantly better than that of the electrodes in Comparative Examples 1 to 3, indicating that the cyclic stability is higher, and the cyclic voltammetry curves of the electrodes in Examples 1 to 5 are closer to a "rectangle", and the cyclic reversibility during charge and discharge is better, and the properties are closer to an ideal supercapacitor (an ideal double-layer capacitor can quickly and evenly form a double-layer capacitor at the electrode-solution interface, so its cyclic voltammetry curve is a "rectangle" with good cyclic reversibility, and the larger the area enclosed by the cyclic voltammetry curve, the higher the specific capacitance of the electrode material).

[0121] 2) Constant current charge and discharge test: The electrodes in Examples 1 to 5 and Comparative Examples 1 to 3 were subjected to constant current charge and discharge tests using an electrochemical workstation model chi660e. The charge and discharge potential range was -1V to 0V, and the current density was 1A / g. The constant current charge and discharge curves obtained are shown in FIG. Figure 3 shown.

[0122] Depend on Figure 3 It can be seen that:

[0123] a) The discharge time of the electrodes in Examples 1 to 5 is significantly longer than that of the electrodes in Comparative Examples 1 to 3, and the specific capacitance is significantly improved compared to the electrodes made of porous carbon materials obtained by direct pyrolysis, KCl and K2CO3 activation, and the charge and discharge performance is very superior;

[0124] b) As the proportion of K2CO3 in the activator increases, the specific capacity of the electrode also increases. The electrode in Example 1 (KCl:K2CO3=1:5) has the longest discharge time and the highest specific capacitance value, reaching 252.0F / g, which is consistent with the cyclic voltammetry test results. In contrast, the specific capacities of the electrodes made of porous carbon materials obtained by direct pyrolysis, KCl and K2CO3 are only 47.7F / g, 71.3F / g and 191.3F / g.

[0125] 3) Specific capacitance rate performance test: The specific capacitance-current density relationship curves of the electrodes in Examples 1 to 5 and Comparative Examples 1 to 3 were tested under the conditions of charge and discharge potential range of -1V to 0V and current density of 0.5A / g, 1A / g, 2A / g, 5A / g, 10A / g and 20A / g using an electrochemical workstation model chi660e. The test results are shown in Figure 4 shown.

[0126] Depend on Figure 4 It can be seen that: as the current density increases, the specific capacity value of the electrode shows a downward trend. Combined with the capacity retention rate in Table 1, at a high current density of 20 A / g, except that the specific capacitance of the electrode in Example 5 is slightly lower than that of the electrode in Comparative Example 3, the specific capacity values ​​and capacity retention rates of the electrodes in Examples 1 to 4 at high current density are higher than those of the electrodes in Comparative Examples 1 to 3.

[0127] 4) Electrochemical impedance test: The electrodes in Examples 1 to 5 and Comparative Examples 1 to 3 were subjected to electrochemical impedance tests using an electrochemical workstation model chi660e. The frequency range of the AC potential wave was 0.1 Hz to 100000 Hz. The real-time open circuit voltage was obtained from the electrochemical workstation, and the electrochemical impedance spectrum curve was obtained. The test results are shown in FIG. Figure 5 shown.

[0128] Depend on Figure 5 It can be seen that:

[0129] a) The electrochemical impedance spectroscopy curves of the electrodes in Examples 1 to 5 conform to the typical trend of porous carbon electrode materials. Compared with the electrodes in Comparative Examples 1 to 3, the straight lines of the electrodes in Examples 1 to 5 are approximately vertical in the low-frequency region, indicating that the material has good capacitance diffusion and has ideal double-layer capacitance characteristics; in the high-frequency region, the intercept with the real axis X-axis represents the equivalent series resistance of the electrode, that is, the internal resistance of the electrode itself and the contact resistance with the electrolyte. The equivalent series resistance of the electrodes in Examples 1 to 5 is significantly lower than that of the electrodes in Comparative Examples 1 and 2, which is beneficial to improving the power density and rate performance of the supercapacitor;

[0130] b) The equivalent series resistance of the electrodes in Examples 1 to 4 is mostly close to that of the electrode in Comparative Example 3, and the equivalent series resistance of the electrode in Example 5 is slightly higher than that of the electrode in Comparative Example 3, which results in the rate performance of the electrode in Example 5 being slightly lower than that of the electrode in Comparative Example 3; in addition, in the medium and high frequency region, the radius of the ring of the electrochemical impedance spectrum curve of the electrodes in Examples 1 to 5 is also significantly smaller than that of the electrodes in Comparative Examples 1 to 3, indicating that the charge transfer resistance of the electrodes in Examples 1 to 5 is also significantly lower than that of the electrodes in Comparative Examples 1 to 3;

[0131] In general, the electrode in Example 1 has the lowest comprehensive impedance, which is consistent with Figure 4 The test results of the maximum capacity retention rate of the electrode in Example 1 are consistent.

[0132] 5) Electrochemical cycle stability test of the electrode in Example 1 at different scan rates and different current densities:

[0133] a) Cyclic voltammetry test: The electrode in Example 1 was subjected to cyclic voltammetry test using an electrochemical workstation model chi660e. The scanning potential range was -1 V to 0 V, and the scanning rates were 5 mV / s, 10 mV / s, 20 mV / s, 50 mV / s, 100 mV / s and 200 mV / s, respectively. The cyclic voltammetry curves obtained at different scanning rates are shown in the figure below. Figure 6 shown.

[0134] Depend on Figure 6It can be seen that: at a scan rate of 5mV / s to 200mV / s, the cyclic voltammetry curve of the electrode generally presents a "rectangular" shape, indicating that the double-layer capacitance behavior is dominant and the electrode has good cycle reversibility during charge and discharge; as the scan rate decreases, the symmetry is further improved, closer to a "rectangle", the cycle reversibility of the electrode during charge and discharge is further improved, and the properties are closer to an ideal supercapacitor.

[0135] b) Constant current charge and discharge test: The electrode in Example 1 was subjected to constant current charge and discharge test using an electrochemical workstation model chi660e. The charge and discharge potential range was -1V to 0V, and the current densities were 0.5A / g, 1A / g, 2A / g, 5A / g, 10A / g and 20A / g, respectively. The constant current charge and discharge curves of the electrode at different current densities are shown in Figure 2. Figure 7 shown.

[0136] Depend on Figure 7 It can be seen that: with the increase of current density, the specific capacity value of the electrode decreases, but its voltage changes linearly with time, and the constant current charge and discharge curve always maintains a symmetrical "isosceles triangle", indicating that the charge and discharge reversibility of the electrode is good. At a current density of 1A / g, the specific capacitance is as high as 252.0F / g. When the current density is increased to 20A / g, it still has a capacity retention rate of up to 80.1%, which meets the requirements of an ideal supercapacitor for good energy storage characteristics and high rate performance.

[0137] In summary, compared with the electrodes made of porous carbon materials obtained by direct pyrolysis, KCl and K2CO3 activation (Comparative Examples 1 to 3), the electrode made of the porous carbon material obtained in Example 1 has a higher specific capacity value, more stable properties and lower internal resistance, indicating that the comprehensive electrochemical performance of the porous carbon material is significantly improved.

[0138] 6) Performance test of the electrodes in Examples 5 to 9 and Comparative Examples 1 to 3:

[0139] a) Cyclic voltammetry test: The electrodes in Examples 5 to 9 and Comparative Examples 1 to 3 were subjected to cyclic voltammetry tests using an electrochemical workstation model chi660e. The scanning potential range was -1 V to 0 V, and the scanning speed was 10 mV / s. The obtained cyclic voltammetry curves are shown in FIG. Figure 8 shown.

[0140] Depend on Figure 8It can be seen that the area enclosed by the cyclic voltammetry curves of the electrodes in Examples 5 to 9 is significantly larger than that of the electrodes in Comparative Examples 1 to 3, indicating that the electrodes in Examples 5 to 9 have higher specific capacity values; as the proportion of KCl in the activator increases, the specific capacity value of the electrode also increases, and the cyclic voltammetry curve of the electrode in Example 9 (KCl:K2CO3=5:1) has the largest enclosed area and the highest specific capacitance; in addition, the symmetry of the cyclic voltammetry curves of the electrodes in Examples 5 to 9 is significantly better than that of the electrodes in Comparative Examples 1 to 3, indicating that they have better cycle stability, and the cyclic voltammetry curves of the electrodes in Examples 5 to 9 are closer to a rectangle, the cycle reversibility during charge and discharge is better, and the properties are closer to an ideal supercapacitor.

[0141] b) Constant current charge and discharge test: The electrodes in Examples 5 to 9 and Comparative Examples 1 to 3 were subjected to constant current charge and discharge tests using an electrochemical workstation model chi660e. The charge and discharge potential range was -1V to 0V, and the current density was 1A / g. The constant current charge and discharge curves obtained are shown in FIG. Fig. 9 shown.

[0142] Depend on Fig. 9 It can be seen that the discharge time of the electrodes in Examples 5 to 9 is significantly longer than that of the electrodes in Comparative Examples 1 to 3, and the specific capacitance is significantly improved compared with the electrodes made of porous carbon materials obtained by direct pyrolysis, KCl and K2CO3 activation, and the charge and discharge performance is very superior; combined with the specific capacitance of 1A / g in Table 1, as the proportion of KCl in the activator increases, the specific capacity value of the electrode also increases. The electrode in Example 9 (KCl:K2CO3=5:1) has the longest discharge time and the highest specific capacitance value, reaching 260.2F / g, which is consistent with the cyclic voltammetry test results; in contrast, the specific capacities of the electrodes made of porous carbon materials obtained by direct pyrolysis, KCl and K2CO3 activation are only 47.7F / g, 71.3F / g and 191.3F / g.

[0143] c) Capacitance rate performance test: The specific capacity-current density relationship curves of the electrodes in Examples 5 to 9 and Comparative Examples 1 to 3 were tested under the conditions of a charge and discharge potential range of -1 V to 0 V and current densities of 0.5 A / g, 1 A / g, 2 A / g, 5 A / g, 10 A / g and 20 A / g using an electrochemical workstation model chi660e. The test results are shown in Fig.10 shown.

[0144] Depend on Fig.10It can be seen that: as the current density increases, the specific capacity value of the electrode shows a downward trend. Combined with the capacity retention rate in Table 1, at a high current density of 20 A / g, the specific capacity values ​​and capacity retention rates of the electrodes in Examples 5 to 9 are significantly higher than those of the electrodes in Comparative Examples 1 and 2; at low current density, although the electrode in Example 9 has the highest specific capacity value (290 F / g at 0.5 A / g), the capacity retention rate at high current density is the lowest, slightly lower than that of the electrode in Comparative Example 3.

[0145] d) Electrochemical impedance test: The electrodes in Examples 5 to 9 and Comparative Examples 1 to 3 were subjected to electrochemical impedance tests using an electrochemical workstation model chi660e. The frequency range of the AC potential wave was 0.1 Hz to 100,000 Hz. The real-time open circuit voltage was obtained from the electrochemical workstation, and the electrochemical impedance spectrum curve was obtained. The test results are shown in FIG. Fig.11 shown.

[0146] Depend on Fig.11 It can be seen that the impedance curves of the electrodes in Examples 5 to 9 conform to the typical trend of porous carbon electrode materials. Compared with the electrodes in Comparative Examples 1 to 3, the straight lines of the electrodes in Examples 5 to 9 are approximately vertical in the low-frequency region, indicating that the material has good capacitance diffusion and has ideal double-layer capacitance characteristics; in the high-frequency region, the intercept with the real axis X-axis represents the equivalent series resistance of the electrode, that is, the internal resistance of the electrode itself and the contact resistance with the electrolyte. The equivalent series resistance of the electrodes in Examples 5 to 8 is significantly lower than that of the electrodes in Comparative Examples 1 and 2, and is close to that of the electrodes in Comparative Example 3, which is beneficial to improving the power density and rate performance of the supercapacitor; the equivalent series resistance of the electrode in Example 9 is the largest, which leads to poor rate performance of the electrode in Example 9, which is slightly lower than that of the electrode in Comparative Example 3, which is consistent with Fig.10 The specific capacity rate performance test results are consistent; in addition, in the medium and high frequency region, the ring radius of the electrochemical impedance spectrum curve of the electrodes in Examples 5 to 9 is also significantly smaller than that of the electrodes in Comparative Examples 1 to 3, indicating that the charge transfer resistance of the electrodes in Examples 5 to 9 is significantly lower than that of the electrodes in Comparative Examples 1 to 3.

[0147] 7) Electrochemical cycle stability test of the electrode in Example 9 at different scan rates and different current densities:

[0148] a) Cyclic voltammetry test: The electrode in Example 9 was subjected to cyclic voltammetry test using an electrochemical workstation model chi660e. The scanning potential range was -1 V to 0 V, and the scanning rates were 5 mV / s, 10 mV / s, 20 mV / s, 50 mV / s, 100 mV / s and 200 mV / s, respectively. The cyclic voltammetry curves obtained at different scanning rates are shown in the figure below. Fig.12 shown.

[0149] Depend on Fig.12It can be seen that: with the increase of scan rate, the symmetry of the cyclic voltammetry curve of the electrode is improved, closer to a "rectangle", the cycle reversibility of the electrode during charge and discharge is better, and the properties are closer to an ideal supercapacitor.

[0150] b) Constant current charge and discharge test: The electrode in Example 9 was subjected to constant current charge and discharge test using an electrochemical workstation model chi660e. The charge and discharge potential range was -1V to 0V, and the current densities were 0.5A / g, 1A / g, 2A / g, 5A / g, 10A / g and 20A / g, respectively. The constant current charge and discharge curves of the obtained electrode at different current densities are shown in Figure 1. Fig.13 shown.

[0151] Depend on Fig.13 It can be seen that: with the increase of current density, the specific capacity value of the electrode decreases, but the constant current charge and discharge curve always maintains a symmetrical "isosceles triangle", indicating that the charge and discharge reversibility of the electrode is good.

[0152] In summary, compared with the electrode made of porous carbon material obtained by direct pyrolysis, KCl and K2CO3 activation, the electrode made of porous carbon material obtained in Example 9 has a higher specific capacity although the comprehensive impedance is increased.

[0153] 8) Performance test of the electrodes in Example 1, Example 9 and Comparative Examples 4 to 6:

[0154] a) Cyclic voltammetry test: The electrodes in Example 1, Example 9 and Comparative Examples 4 to 6 were subjected to cyclic voltammetry test using an electrochemical workstation model chi660e, with a scanning potential range of -1 V to 0 V and a scanning speed of 10 mV / s. The obtained cyclic voltammetry curves are shown in FIG. Fig.14 shown.

[0155] Depend on Fig.14 It can be seen that the area enclosed by the cyclic voltammetry curves of the electrodes in Examples 1 and 9 is significantly larger than that of the electrodes in Comparative Examples 5 and 6, indicating that the electrodes in Examples 1 and 9 have higher specific capacity values. Although the cyclic voltammetry curve of the electrode in Comparative Example 4 (KOH activation) has a larger enclosed area, the yield of the porous carbon material is extremely low, only 21.9%, and the economy and practicality are poor. The operating process of KOH activation is relatively complicated, the cost is high, and it is easy to corrode equipment and poison the environment. In addition, the symmetry of the cyclic voltammetry curves of the electrodes in Examples 1 and 9 is better than that of the electrodes in Comparative Examples 4 to 6, indicating that their cycle stability is higher, and the cyclic voltammetry curves of the electrodes in Examples 1 and 9 are closer to a "rectangle", the cycle reversibility during charge and discharge is better, and the properties are closer to an ideal supercapacitor.

[0156] b) Constant current charge and discharge test: The electrodes in Example 1, Example 9 and Comparative Examples 4 to 6 were subjected to constant current charge and discharge tests using an electrochemical workstation model chi660e. The charge and discharge potential range was -1V to 0V, and the current density was 1A / g. The constant current charge and discharge curves obtained are shown in FIG. Fig.15 shown.

[0157] Depend on Fig.15 It can be seen that the discharge time of the electrodes in Examples 1 and 9 is significantly longer than that in Comparative Examples 5 and 6, and the specific capacitance is significantly improved compared to the electrodes made of porous carbon materials activated by traditional ZnCl2 and H3PO4, and the charge and discharge performance is very superior. Although the electrode in Comparative Example 4 (KOH activation) has a longer discharge time, the yield of the porous carbon material is extremely low, only 21.9%, and the economy and practicality are poor; combined with the yield in Table 1 and the specific capacitance of 1A / g, Example 9 (KCl:K2CO3=5:1) The electrode in has the longest discharge time, the specific capacitance value is as high as 260.2F / g, and the yield of porous carbon material is as high as 60.4%. The specific capacitance value of the electrode in Example 1 (KCl:K2CO3=1:5) reaches 252.0F / g, and the yield of porous carbon material is as high as 57.9%. The yields of porous carbon materials activated by KOH, ZnCl2 and H3PO4 are 21.9%, 62.4% and 65.3% respectively, and the specific capacities of the prepared electrodes are 328.6F / g, 125.9F / g and 47.9F / g respectively.

[0158] c) Capacitance rate performance test: The specific capacity-current density relationship curves of the electrodes in Example 1, Example 9 and Comparative Examples 4 to 6 were tested under the conditions of a charge and discharge potential range of -1V to 0V and current densities of 0.5A / g, 1A / g, 2A / g, 5A / g, 10A / g and 20A / g using an electrochemical workstation model chi660e. The test results are shown in Fig.16 shown.

[0159] Depend on Fig.16It can be seen that: as the current density increases, the specific capacity value of the electrode shows a downward trend. Combined with the capacity retention rate in Table 1, at a high current density of 20A / g, the specific capacity value and capacity retention rate of the electrode in Example 1 are significantly higher than those of the electrodes in Comparative Examples 4 to 6. Combined with Table 1, the capacity retention rate of the electrode in Example 1 at a high current density reaches 80.1%, and the specific capacity value is 252.0F / g. The capacity retention rates of the electrodes in Comparative Examples 4 to 6 are 72.0%, 71.5% and 66.8%, respectively. Although Example 9 The capacity retention rate of the electrode in Example 4 is not high, only 55.3%, but its specific capacity value at high current density is still 145.0F / g, while the specific capacity values ​​of the electrodes in Comparative Examples 5 and 6 are only 90.0F / g and 32.0F / g. Although the electrode in Comparative Example 4 (KOH activation) has a higher specific capacity value at high current density, the yield of the porous carbon material is extremely low, only 21.9%, and the economy and practicality are poor. In addition, the operating process of KOH activation is relatively complicated, the cost is high, and it is easy to corrode equipment and poison the environment.

[0160] d) Electrochemical impedance test: The electrodes in Example 1, Example 9 and Comparative Examples 4 to 6 were subjected to electrochemical impedance tests using an electrochemical workstation model chi660e. The frequency range of the AC potential wave was 0.1 Hz to 100000 Hz. The real-time open circuit voltage was obtained from the electrochemical workstation, and the electrochemical impedance spectrum curve was obtained. The test results are shown in FIG. Fig.17 shown.

[0161] Depend on Fig.17 It can be seen that the impedance curves of the electrodes in Examples 1 and 9 conform to the typical trend of porous carbon electrode materials. Compared with the electrodes in Comparative Examples 4 to 6, the straight lines of the electrodes in Examples 1 and 9 are approximately vertical in the low-frequency region, indicating that the material capacitance diffusion is good and has ideal double-layer capacitance characteristics; in the high-frequency region, the intercept with the real axis X-axis represents the equivalent series resistance of the electrode, that is, the internal resistance of the electrode itself and the contact resistance with the electrolyte. The equivalent series resistance of the electrode in Example 1 is significantly lower than that of the electrodes in Comparative Examples 4 and 5, and is close to that of the electrode in Comparative Example 6, which is beneficial to improving the power density and rate performance of the supercapacitor; the equivalent series resistance of the electrode in Example 9 is the largest, which leads to the poor rate performance of the electrode in Example 9; in addition, in the medium and high frequency regions, the annular radius of the electrochemical impedance spectroscopy curves of the electrodes in Examples 1 and 9 is also significantly smaller than that of the electrodes in Comparative Examples 4 to 6, indicating that the charge transfer resistance of the electrodes in Examples 1 and 9 is significantly lower than that of the electrodes in Comparative Examples 4 to 6; on the whole, the comprehensive impedance of the electrode in Example 1 is the lowest.

[0162] The yield and electrode performance summary of the porous carbon materials in Examples 1 to 9 and Comparative Examples 1 to 6 are shown below:

[0163] Table 1 Summary of the yield and electrode performance of porous carbon materials

[0164]

[0165]

[0166] Note:

[0167] The calculation formula of the porous carbon material yield is: porous carbon material yield (%) = (weight of porous carbon material / weight of 2,9-dimethylquinacridone) × 100%.

[0168] It can be seen from Table 1 that although the high-cost and highly corrosive KOH and K2CO3 molten salt activation effects are obvious, the yield of porous carbon materials is generally low. Although direct pyrolysis, KCl, H3PO4 and highly toxic ZnCl2 activation have high yields of porous carbon materials, the electrochemical properties of porous carbon materials are generally poor. In contrast, the new green activator (KCl+K2CO3) involved in Examples 1 to 9 has a lower cost, and the prepared porous carbon materials have a higher yield of porous carbon materials (close to 60%), and the specific capacity value and capacity retention rate of the prepared electrodes are generally higher, and the electrochemical performance is better.

[0169] In summary, the cost of the activator used in the present invention is reduced, which solves the problems of high cost, low yield, strong corrosiveness and environmental toxicity of traditional activators (KOH, K2CO3, H3PO4, ZnCl2, etc.), and the one-step pyrolysis preparation method is simpler than the traditional method. The prepared porous carbon material has a high yield and stable physicochemical properties. The prepared electrode has low impedance, high specific capacitance, excellent rate performance and good cycle stability, which improves the electrochemical properties of the porous carbon material.

[0170] Note:

[0171] 1) Although only the case of pyrolysis temperature of 700°C is listed in Examples 1 to 9, in fact, when the pyrolysis temperature is in the range of 500°C to 1000°C, the prepared porous carbon materials all have excellent properties;

[0172] 2) Although Examples 1 to 9 only list the case where the ratio of the mass of 2,9-dimethylquinacridone to the total mass of KCl and K2CO3 is 1:5, in fact, when the ratio of the mass of 2,9-dimethylquinacridone to the total mass of KCl and K2CO3 is in the range of 1:1 to 20, the prepared porous carbon materials all have excellent properties.

[0173] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a porous carbon material, characterized in that: The following steps are involved: The porous carbon material is obtained by mixing 2,9-dimethylquinacridone, KCl and K2CO3 and placing them in a protective atmosphere for pyrolysis.

2. The method for preparing a porous carbon material according to claim 1, characterized in that: The ratio of the mass of the 2,9-dimethylquinacridone to the total mass of KCl and K2CO3 is 1:1-20.

3. The method for preparing a porous carbon material according to claim 1 or 2, characterized in that: The mass ratio of KCl to K2CO3 is 1:0.1-10.

4. The method for preparing a porous carbon material according to claim 1 or 2, characterized in that: The pyrolysis is carried out at a temperature of 500° C. to 1000° C., and the pyrolysis time is 1 hour to 3 hours.

5. The method for preparing a porous carbon material according to claim 1 or 2, characterized in that: The product obtained by the pyrolysis is further acid-washed, water-washed and dried.

6. A porous carbon material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 5.

7. An electrode, characterized in that: The porous carbon material according to claim 6 is included.

8. The electrode according to claim 7, characterized in that: The electrode also comprises a conductive component and a binder.

9. A method for preparing an electrode as claimed in claim 8, characterized in that: The following steps are involved: 1) mixing the porous carbon material, the conductive component and the binder solution, and then adding a demulsifier to demulsify to obtain a coating material; 2) Apply the coating material on the carrier, dry it, and press it into sheets to obtain the electrode.

10. A supercapacitor, characterized in that: Comprising the electrode according to claim 7 or 8.

Citation Information

Patent Citations

  • Preparation method and application of starch-based carbon aerogel

    CN114572985A